ANALISIS STUDI LITERATUR PERAN SNMP DALAM MONITORING KINERJA DAN KETERSEDIAAN JARINGAN TELKOMUNIKASI - Meidina Agnesia; Sri Yusnita; Afrizal Yuhanef; Yulindon Khaidir (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
The increasing complexity, heterogeneity, and large-scale nature of modern telecommunication networks require a monitoring mechanism capable of ensuring continuous network performance and service availability. Although modern approaches such as streaming telemetry and network observability provide higher data granularity, Simple Network Management Protocol (SNMP) remains widely used due to its lightweight design, standardization, and multi-vendor compatibility. This study aims to analyze the role of SNMP in monitoring network performance and availability in telecommunication systems. The research employed a structured literature review approach by collecting, selecting, and synthesizing relevant studies published within the last five years. The results indicate that SNMP remains effective for monitoring key performance parameters, including throughput, latency, packet loss, CPU utilization, interface status, uptime, and fault notifications. Its major strength lies in supporting interoperable monitoring across heterogeneous multi-vendor infrastructures. However, limitations were identified in terms of polling scalability, data granularity, and real-time traffic visibility in modern cloud, SDN, edge, and IoT-based environments. This study concludes that SNMP remains strategically relevant as a baseline monitoring layer and is most effective when integrated with streaming telemetry in a hybrid monitoring architecture.